Rates of Medically Attended RSV Among US Adults: A Systematic Review and Meta-analysis - McLaughlin, John M; Khan, Farid; Begier, Elizabeth; Swerdlow, David L; Jodar, Luis; Falsey, Ann R (Open forum infectious diseases, 2022)
Abstract Background Adult respiratory syncytial virus (RSV) vaccines are in the late stages of development. A comprehensive synthesis of adult RSV burden is needed to inform public health decision-making. Methods We performed a systematic review and meta-analysis of studies describing the incidence of medically attended RSV (MA-RSV) among US adults. We also identified studies reporting nasopharyngeal (NP) or nasal swab reverse transcription polymerase chain reaction (RT-PCR) results with paired serology (4-fold-rise) or sputum (RT-PCR) to calculate RSV detection ratios quantifying improved diagnostic yield after adding a second specimen type (ie, serology or sputum). Results We identified 14 studies with 15 unique MA-RSV incidence estimates, all based on NP or nasal swab RT-PCR testing alone. Pooled annual RSV-associated incidence per 100 000 adults ≥65 years of age was 178 (95% CI, 152‒204; n = 8 estimates) hospitalizations (4 prospective studies: 189; 4 model-based studies: 157), 133 (95% CI, 0‒319; n = 2) emergency department (ED) admissions, and 1519 (95% CI, 1109‒1929; n = 3) outpatient visits. Based on 6 studies, RSV detection was ∼1.5 times higher when adding paired serology or sputum. After adjustment for this increased yield, annual RSV-associated rates per 100 000 adults age ≥65 years were 267 hospitalizations (uncertainty interval [UI], 228‒306; prospective: 282; model-based: 236), 200 ED admissions (UI, 0‒478), and 2278 outpatient visits (UI, 1663‒2893). Persons <65 years with chronic medical conditions were 1.2−28 times more likely to be hospitalized for RSV depending on risk condition. Conclusions The true burden of RSV has been underestimated and is significant among older adults and individuals with chronic medical conditions. A highly effective adult RSV vaccine would have substantial public health impact.